Psychological Foundations of Developing a Sense of Humanity in Young Students - Karimova Madina Kholmuratovna (European Science Publishing, 2023)
This article is about the moral feelings of the person and the factors of their development in students, the sense of humanity and its social importance. It was discussed about turning humanitarianism, which is considered a moral feeling in students, into life habits.
Keywords: Moral feeling, morality, humanity, teenager, value, duty, student period.